Teachers Leading Beyond the Classroom - Warren, Louis L. (Advances in Social Sciences Research Journal, 2023)
The role of teachers has evolved significantly, extending far beyond the traditional confines of the classroom. This paper explores the multifaceted role of teacher leaders who embrace a more comprehensive and influential position within the education system. Teacher leadership is a term that encompasses various roles and responsibilities, and its definition can vary depending on the organizational structure of the school. This study delves into how teacher leaders catalyze change within their classrooms and at broader levels, such as the school, district, and national levels. Teachers leading beyond the classroom underscores the essential role that teacher leaders play in shaping the future of education by leveraging their passion, expertise, and experience to bring about positive change in various facets of the educational system. It emphasizes the need for schools to recognize and harness the potential of teacher leaders to create a more dynamic, inclusive, and effective learning environment for all stakeholders in education.